DAMPAK KELAPA SAWIT TERHADAP PEREKONOMIAN MASYARAKAT DI KABUPATEN ROKAN HILIR RIAU - Meri Syafitri; Alfi Rahmi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
The research aims to find out how the palm oil mill workforce and how the production of oil palm smallholders contributes to the income of employees who work in oil palm plantations. The Rokan Hilir method used is interviews and documentation. Sampling was done purposively. The productivity of the palm oil mills is very high because the oil palm farmers are always pressing their superiors to achieve the targets they achieve. Meanwhile, oil palm farmers who have to reach the target of factory employees are unable to calculate how much % of their income is very large, so that the used palm fruit piles up in the factory until they have to fertilize the used palm fruit which is commonly called by the local community as janjangan. The saplings are thrown into the forest or into the oil palm, which the smallholders haven't harvested yet, why throw it back into the oil palm because the saplings can fertilize other palm oil. The research was conducted 3 times to interview employees of the palm oil mill. the pressure of oil palm farmers to achieve the target because their income is already optimal.